Factors Predictive of High-Risk Adenomas at the Third Colonoscopy after Initial Adenoma Removal - Chung, Sook Hee; Park, Soo Jung; Cheon, Jae Hee; Park, Mi Sung; Hong, Sung Pil; Kim, Tae Il; Kim, Won Ho (Journal of Korean medical science, 2013)
Evaluating predictive factors for high-risk adenomas at the third colonoscopy based on two prior colonoscopies may help evaluate high-risk adenoma at the third colonoscopy. We analyzed clinical data of 131 patients at Severance Hospital from January 1997 to January 2011. All of them underwent two subsequent colonoscopies after removal of adenomas during an initial colonoscopy. Among 20 patients with high-risk adenoma at the first and second colonoscopies, 10 (50%) patients had high-risk adenoma at the third colonoscopy. Among the 67 patients who had high-risk adenoma only once at the first or second colonoscopy, 15 (22.4%) patients had high-risk adenoma at the third colonoscopy but among the 44 patients without high-risk adenoma at the first and second colonoscopies, only 1 (2.3%) patient had high-risk adenoma at the third colonoscopy (P < 0.001). A multivariate time dependent covariate Cox regression analysis confirmed that high-risk adenoma at the first and/or second colonoscopy (HR, 9.56; 95% CI, 2.37-38.54; P = 0.002) was independent predictor of high-risk adenoma at the third colonoscopy. Given these findings, data from two prior colonoscopies, not one prior examination, may help identify high-risk populations at the third colonoscopy who require careful colonoscopic surveillance.